EFFECT OF EXPORT IMPORT AND INVESTMENT ON ECONOMIC GROWTH IN INDONESIA (VECM ANALYSIS METHOD) - Hijri Juliansyah; Yudha Ganesha; Ichsan Ichsan; Fanny Nailufar; Sari Yulis Terfiadi (LPPM Universitas Malikussaleh, 2022)
This study aims to know the effect of export, import and investment on economic growth in Indonesia. This study employis secondary data in the period 1967-2020 obrained from the World Bank. The data is analyzed by using Vector Error Correction Method (VECM). All tests used in this study are unit root test, lag length criterion test, cointegration test, Granger causality test and VAR stability test. The results showed that the export and import of Indonesia have a positive and insignificant effect on Indonesia economic growth both in short run and long run. Investment has a negative and insignificant effect on economic growth both in short run and long run in Indonesia.